Johor Corporation: a study on collectivism and decision making / Farhana Zainuddin - Zainuddin, Farhana (Faculty of Business and Management, 2012)
In the era of globalization, understanding of cultural differences in decision making becomes increasingly important not just for personal interest but also for designing effective international management program for one organizational. Hence, the purpose of this study is to explore the relationship between collectivism and decision making which the collectivism dimension is one of the Greet Hofstede’s cultural frameworks. Thus, this study will give benefit not just to the researcher but also to the other people who have desires to have knowledge related to this study. To gather information from respondents which are among employees in Johor Corporation, the questionnaire was distributed to 50 respondents with 28 questions have been asking in the questionnaire. The list of questions consists of 4 parts which are vertical and horizontal dimension, decision making and demographic. After the data have been collected, the software of SPSS version 15 was conducted the result. Therefore, the result indicates the relationship among variables.